Economic evaluation of surface and subsurface drip fertigated basmati rice-wheat-mungbean cropping system under different irrigation scheduling - MEENA, VED PRAKASH; Lal, Khajanchi; MEENA, CHANDRA PRAKASH; KHANNA, MANOJ; PS BRAHMANAND; ARPULA, SAIRAM; JAIN, NIVETA; SHEKHAWAT, KAPILA; MEENA, MAHESH CHAND; SUDHISHRI, SUSAMA; BRAR, AS BRAR; MEENA, RAMESHI (The Indian Journal of Agricultural Sciences, 2026)
Low water use efficiency and increasing water scarcity require efficient irrigation management for sustaining the productivity of the prominent basmati rice–wheat-mungbean cropping system of Indo-Gangetic plains. This field study evaluated the productivity and economic feasibility of drip fertigated basmati rice (Oryza sativa L.) both direct seeded (DSR) and transplanted (TPR)-wheat (Triticum aestivum L.)-mungbean (Vigna radiata L.) cropping system irrigated through surface (SD) and subsurface drip (SSD) at three irrigation scheduling [1.2, 1.4 and 1.6 crop evapotranspiration (ETc) in rice, corresponding ETc 0.6, 0.8 and 1.0 in wheat and mungbean] in comparison with the control (flood irrigation with a 100% recommended dose of NPK fertilizers) However; transplanted rice was irrigated only through subsurface drip (SSD-TPR). Raising irrigation schedule from 1.2 to 1.4 ETc in rice and from 0.6 to 0.8 ETc in wheat and mungbean improved the crop yields of rice, wheat, mungbean and system rice equivalent yield (SREY) by 19.2, 36.6, 20.3 and 23.7%, respectively. System productivity under SSD-DSR, SSD-TPR and SD-DSR was 9.04, 8.96 and 8.55 Mg ha-1, respectively and found comparable. At 0.8/1.4 ETc, fertigation with 100% NPK produced average SREY (9.49 Mg ha-1) statistically higher to that of the conventional practice (9.16 Mg ha-1). Economic indicators, including net income and benefit–cost ratio (BCR) at different irrigation schedule were found in the order 1.4=1.6>1.2 ETc in rice and 0.8=1.0>0.6 in wheat and mungbean. Among the crops, net income and BCR were in the order: rice>wheat>mungbean. Under SSD-DSR with 1.4 ETc in rice, SSD in wheat and mungbean at 0.8 ETc and overall system (0.8/1.4 ETc), net income was 12.1, 41.2, 57.0 and 27.5% greater, respectively, than the conventional approach. At 0.8/1.4 ETc, SSD-DSR recorded a higher BCR (2.03) compared to SSD-TPR (1.91); at 1.0/1.6 ETc, SD-DSR (1.89) and the conventional system (1.74).